Effects of AlCl3 on the Enzymatic Antioxidants of Wister Rats Treated with Moringa oleifera Seed Extracts - Yusufu, Dawoye; Zinas, Simon Teza; Habibu, Bilyaminu; Amen, Ananias; Umaru, Isaac John; Ejeh, Yakubu Ojochenemi; Grace, Onwubiko N.; Henry, Onwubiko A.; Audu, Anthony Mishara; Umaru, Kerenhappuch Isaac (African Journal of Sciences and Traditional Medicine, 2024)
Determination of Malondialdehyde, MDA in blood plasma or tissue homogenates is one of the useful methods to predict the oxidative stress levels. The current study investigates the ameliorative effects of the seed extracts of Moringa oleifera on 35 albino rats induced with AlCl3 toxicity. Biomarkers of oxidative stress (Superoxide Dismutase, SOD; Catalase, CAT; Glutathione Peroxidase, GPx and Malondialdehyde, MDA were assayed. The plant seed extracts were shown to reduce the levels of MDA increased by AlCl3. AlCl3 caused decrease in (glutathione peroxidase) GPx levels as it causes MDA to significantly get elevated. The results showed that GPx decreased from 9.48 ± 0.86 to 6.68 ± 1.73 but upon treatments with 100 mg/kg bw of M. oleifera, GPx levels increased to 8.84 ± 0.86 (ethanol) and 8.96 ± 0.86 (aqueous). Increasing the concentrations of the extracts further increased the GPx levels while MDA were reduced.